Study on the Correlation Between Exchange Rate Fluctuations and the Global Economy Based on Macroeconomic Models - Meng, Qiantong (International Journal of Global Economics and Management, 2024)
In the context of global economic integration, exchange rates act as a bridge connecting national economies, and fluctuations in exchange rates directly impact the global economy. An exchange rate is the ratio at which one currency can be exchanged for another, representing the value of one country’s currency against another’s. Additionally, exchange rates serve as a financial tool for countries to achieve political objectives. This study deeply analyzes the correlation between exchange rate fluctuations and the global economy based on macroeconomic models and identifies the multiple factors influencing exchange rate changes. The research finds that exchange rate fluctuations affect international trade competitiveness and the direction of capital flows. Through the transmission mechanisms of financial markets, they also impact key economic indicators such as global economic growth, employment levels, and price stability. Thus, a systematic analysis of the complex interactions between exchange rate changes and the global economy is essential to address global economic challenges and promote the coordinated development of national economies.